From dilute to dense gas-solid flows simulation: the CFB riser case study - Venturi, Diego Nei (2020)
The importance of gas-solid flows in industry is never overestimated, they are present in many different production sectors and equipment. When in the vertical ascending configuration, such flows may appear in many different patterns, but the subjects of study in the present work will lie mainly on the fast fluidization or pneumatic conveying ones. In the present thesis, the main subject of investigation is on the modeling and simulation of gas-solid flows in CFB risers utilizing CFD. This equipment is commonly utilized for the recovery of heavy petroleum fractions into more usable products such as gasoline and diesel, and has a lot of interest from the oil companies. For this analysis, the UNSCYFL3D code is utilized, which is an already established computational code for the simulation of dilute gas-solid flows. The objective of this thesis is to consolidate a new formulation in the UNSCYFL3D that is suitable also for dense flows, but keeping a reasonably cheap computational cost. To do this, first it was noted from the literature that the gas phase formulation has to be changed into accounting the volume fraction, rather than using the standard single-phase equations. Another important aspect are the particle-particle collisions. It is common that in such cases deterministic collision approaches are used, but the increase in the computational cost may prohibit analysis in large equipment. For this reason, in the present thesis a stochastic model that has not been tested before for dense flows is utilized. Two formulations are summarized and presented in the thesis, one for dilute flows and one for dense flows. Both of them are within the Euler-Lagrange framework, with the point-particle approach. A thorough study is carried out beforehand for dilute flows to assess some late implementations, and to evaluate up to which point the dilute formulation is valid for dense flows. Following that, CFB riser simulations are carried out utilizing both formulations to show the importance of the correct modeling, and the accuracy of the stochastic particle-particle collision model in this condition. In the present thesis, we have shown that the dilute formulation is valid for a solids mass loading of up to 1 kg_part.\kg_ar in horizontal flows, but up to 8 kg_part.\kg_ar in well-distributed vertical ascending flows. However, as in CFB risers the configuration of the geometry encourages the agglomeration of the solids into clusters, even lower solids mass loadings (4 kg_part.\kg_ar) are shown to need the dense formulation. Also, a comparison with experiments and other simulations utilizing deterministic collision approaches, show that the the present formulation is able to correctly predict the dense gas-solid flows in CFD risers up to 22 kg_part.\kg_ar.